Determinants of Accountability in Village Financial Management with Internal Control System as a Moderating Variable (A Study of Villages in Towuti Subdistrict, East Luwu Regency) - Agustina, Irnarezky; Sumarlin, Sumarlin; Jannah, Raodahtul (Phinisi Applied Accounting Journal, 2024)
This study aims to examine the effect of village apparatus competence, financial report presentation, and financial report accessibility on the accountability of village financial management with the internal control system as a moderating variable in villages in Towuti Subdistrict, East Luwu Regency. This research is quantitative in nature. The sampling technique used is purposive sampling, with data collection through questionnaires. The questionnaires were distributed to 18 villages, with a total sample size of 149 respondents. The data analysis was performed using multiple regression analysis and Moderated Regression Analysis (MRA) with SPSS version 26. The results of the study indicate that village apparatus competence and the presentation of financial reports have a positive and significant impact on the accountability of village financial management, while financial report accessibility does not have an impact on the accountability of village financial management. The moderating regression analysis shows that the internal control system is able to moderate the relationship between financial report presentation and the accountability of village financial management, while the internal control system does not moderate the relationship between village apparatus competence and financial report accessibility on the accountability of village financial management. Based on the findings, the implications of this study suggest the need for efforts to improve the transparency and accountability of village financial management by the village apparatus.Penelitian ini bertujuan untuk menguji pengaruh kompetensi aparat desa, penyajian laporan keuangan dan aksesibilitas laporan keuangan terhadap akuntabilitas pengelolaan keuangan desa dengan sistem pengendalian internal sebagai variabel moderasi pada desa se-Kecamatan Towuti Kabupaten Luwu Timur. Penelitian ini merupakan penelitian kuantitatif. Teknik pengambilan sampel dengan menggunakan metode purposive sampling dengan teknik pengumpulan data menggunakan angket / kuesioner. Kuesioner disebar ke 18 desa. Total sampel pada penelitian ini sebanyak 149. Data analisis dengan menggunakan teknik analisis regresi berganda dan analisis regresi moderasi atau Moderate Regression Analisis (MRA) dengan menggunakan aplikasi SPSS versi 26. Hasil dari penelitian ini menunjukkan bahwa kompetensi aparat desa dan penyajian laporan keuangan memilik pengaruh positif dan signifikan terhadap akuntabilitas pengelolaan keuangan desa sedangkan aksesibilitas laporan keuangan tidak berpengaruh terhadap akuntabilitas pengelolaan keuangan desa. Analisis regresi moderasi menunjukkan bahwa sistem pengendalian internal mampu memoderasi hubungan antara penyajian laporan keuangan terhadap akuntabilitas pengelolaan keuangan desa sedangkan sistem pengendalian internal tidak mampu memoderasi hubungan antara kompetensi aparat desa dan aksesibilitas laporan keuangan terhadap akuntabilitas pengelolaan keuangan desa. Berdasarkan hasil penelitian maka implikasi dari penelitian ini diperlukan upaya peningkatan transparansi dan akuntabilitas pengelolaan keuangan desa yang dilakukan oleh aparat desa.